Efektivitas Market Research dalam Meningkatkan Pemahaman Pasar dan Ekspor Produk UMKM Kopi Sidikalang - Br Meliala, Micha Ella; Taufiq, M. (Peneliti.net, 2024)
The diversity of local products produced by entrepreneurs and Micro, Small, and Medium Enterprises (MSMEs) in Indonesia offers a glimpse into the country's cultural richness and economic potential. This article explores the global market potential for MSME-produced coffee powder in Sidikalang City, Indonesia, sourced from high-quality coffee beans cultivated at an elevation of 1500 meters above sea level. Despite the product's high-quality competitiveness, limitations in knowledge and marketing strategies hinder its international market penetration. This research aims to evaluate the effectiveness of market research capabilities and knowledge as tools to support the global expansion of MSME coffee products. Through in-depth analysis, the study provides insights into the potential economic contribution of Indonesia by enhancing the position of local products in the global market. The research findings are expected to establish a strategic foundation for the development of MSME coffee products, thereby contributing to national economic growth